Мастодонт Anancus arvernensis из плиоценовых отложений южной Молдавии - Свистун, В.И. (Вестник зоологии, 1984)
Mastodont Anancus arvernensis from Pliocene Deposits of the Southern Moldavia. Svistun V. L— Vestn. zool., 1984, No. 1. A comparative study of the lower jaw of a tuberculate teeth mastodon found in continental deposits of South Moldavia (village Dermedzhi, Kagul District) showed that it belongs to Anancus arvensis. Suggested geological age —— Middle Pliocene (Rousillon)